2014
DOI: 10.1177/1071100714537630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Posterior Malleolar Fractures and the Posterior Pilon Variant in Operatively Treated Ankle Fractures

Abstract: Level III, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…All these variant fractures underwent open reduction and internal fixation using either a posterolateral or a posteromedial approach, and the investigators reported satisfactory outcomes. A recent study by Switaj et al (32) reported a 20% incidence of posterior malleolus variant (termed the "posterior pilon variant") in operatively treated ankle fractures.…”
Section: Variants Of Posterior Malleolar Fracturementioning
confidence: 99%
“…All these variant fractures underwent open reduction and internal fixation using either a posterolateral or a posteromedial approach, and the investigators reported satisfactory outcomes. A recent study by Switaj et al (32) reported a 20% incidence of posterior malleolus variant (termed the "posterior pilon variant") in operatively treated ankle fractures.…”
Section: Variants Of Posterior Malleolar Fracturementioning
confidence: 99%
“…Haraguchi et al [26] in their study even included PM fractures that carried the entire medial malleolus. Switaj et al [69] and Klammer et al [41] termed the medial extension type of a fracture of the posterior rim (Haraguchi´s type II, Bartoníček´s and Rammelt´s type 3) a "posterior pilon fracture". Weber [77] considers this type as a part of trimalleolar fractures of the ankle.…”
Section: Classificationmentioning
confidence: 99%
“…Accuracy of PM reduction and quality of its fixation were postoperatively assessed on plain radiographs only, without CT follow-up. Only a few studies evaluated one particular type of PM fractures [41,69,77]. Therefore, based on the available literature, it is impossible to develop true evidence-based guidelines for the treatment of PM fractures.…”
Section: Prognosis and Complicationsmentioning
confidence: 99%
“…In the largest series of surgically treated ankle fractures for which fracture characteristics were reported, Switaj et al showed that 50% of the fractures involved the posterior malleolus 11 . Treating physicians must be vigilant in looking for such a fracture, as it may alter their choice of fixation method or approach.…”
Section: Ankle Fractures and Syndesmotic Injuriesmentioning
confidence: 99%